PENGARUH SERVICESCAPE KLASTER UMKM DI KOTA JAMBI TERHADAP KEPUASAN PELANGGAN DENGAN INOVASI PRODUK SEBAGAI MODERASI - Waridin Niam (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
The purpose of this study to examine the influence of services cape and product innovation on customer satisfaction at three food clusters service. Sample consists of 150 respondents that chosen randomly. Data analysis use linier regression. The result showed for the first regression R2 is 75, 4%. Then it followed the function of mediator, it increased R to be 78, 2%. Hence its proved the role of product innovation as mediator variable is found in the model. Due to the data analysis cluster shows its function to facilitate customer’s satisfaction is worked. So the SME should developed their service based on customer need in one hand while local government communicate the cluster and keep manage all the services cape facilities.